Development and Validation of a Risk Prediction Model for Prolonged Hospitalization in Patients With Diabetic Foot Ulcers - Wang, Bingxue; Lin, Ting; Wu, Jing; Gong, Hongping; Ren, Yan; Zha, Panpan; Chen, Lihong; Liu, Guanjian; Chen, Dawei; Wang, Chun; Ran, Xingwu (Sichuan da xue xue bao. Journal of Sichuan University. Yi xue ban, 2024)
To investigate the risk factors associated with prolonged hospitalization in patients diagnosed with diabetic foot ulcers (DFU), to develop a predictive model, and to conduct internal validation of the model. The clinical data of DFU patients admitted to West China Hospital, Sichuan University between January 2012 and December 2022 were retrospectively collected. The subjects were randomly assigned to a training cohort and a validation cohort at a ratio of 7 to 3. Hospital stays longer than 75th percentile were defined as prolonged length-of-stay. A thorough analysis of the risk factors was conducted using the training cohort, which enabled the development of an accurate risk prediction model. To ensure robustness, the model was internally validated using the validation cohort. A total of 967 inpatients with DFU were included, among whom 245 patients were identified as having an extended length-of-stay. The training cohort consisted of 622 patients, while the validation cohort comprised 291 patients. Multivar